(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
This chapter puts forward the implementation of the Japanese philosophy “Kaizen” to apply in the processes of a private medical health service company, with the purpose of increasing quality and satisfaction. The study was developed with the identification of improvement points and priority projects for the company, subsequently it gave way to the creation of control charts by calculating the arithmetic mean (X) and the range (R) of the service attention time with the collection of 100 samples. As a result, it was obtained that the processes are out of control against the changes that are derived from environmental variables.